144 1. Measure theory We can express F (b) − F (a) as a telescoping series F (b) − F (a) = k j=1 F (tj) − F (tj−1). To estimate the size of this sum, let us first consider those j for which tj ∗ ∈ E. Then, by construction, the intervals (tj−1,tj) are disjoint in U. By construction of κ, we thus have j:tj ∗∈E |F (tj) − F (tj−1)| ≤ ε and thus j:t∗∈E j F (tj) − F (tj−1) = O(ε). Next, we consider those j for which tj ∗ ∈ E. By construction, for those j we have F (tj) − F (tj ∗) = (tj − tj ∗)F (tj ∗) + O(ε|tj − tj ∗|) and F (tj ∗) − F (tj−1) = (tj ∗ − tj−1)F (tj ∗) + O(ε|tj ∗ − tj−1|) and thus F (tj) − F (tj−1) = (tj − tj−1)F (tj ∗) + O(ε|tj − tj−1|). On the other hand, from construction again we have [tj−1,tj ] F (y) dy = (tj − tj−1)F (tj ∗) + O(ε|tj − tj−1|) and thus F (tj) − F (tj−1) = [tj−1,tj ] F (y) dy + O(ε|tj − tj−1|). Summing in j, we conclude that j:t∗∈E j F (tj) − F (tj−1) = S F (y) dy + O(ε(b − a)), where S is the union of all the [tj−1,tj] with tj ∗ ∈ E. By construction, this set is contained in [a, b] and contains [a, b]\U. Since U |F (x)| dx ≤ ε, we conclude that S F (y) dy = [a,b] F (y) dy + O(ε). Putting everything together, we conclude that F (b) − F (a) = [a,b] F (y) dy + O(ε) + O(ε|b − a|). Since ε 0 was arbitrary, the claim follows.

Purchased from American Mathematical Society for the exclusive use of nofirst nolast (email unknown) Copyright 2011 American Mathematical Society. Duplication prohibited. Please report unauthorized use to cust-serv@ams.org. Thank You! Your purchase supports the AMS' mission, programs, and services for the mathematical community.